"Beyond Death": John Webster's The Duchess of Malfi and Posthumous Influence. Issue 1 (May 2019) - Lodine-Chaffey, Jennifer
Abstract : This essay argues that John Webster's 1611 drama, The Duchess of Malfi, attests to the power of death to shape selfhood and demonstrates the influence of textual monuments on the living. As Webster notes, posthumous fame is not based solely on its ability to console, but rather on "the dignity of a great example, " which is shown at the end of the play through the Duchess' continuing influence on other characters. Reactions to both her dead body and the edifice constructed in her honor highlight the transformative power of the Duchess' death and monumentalization. Specifically, The Duchess of Malfi offers audiences a gendered type of memorial, one based on the ability of a female character to posthumously influence the actions of others.